Multilingualism and Acculturation in Catalonia: An Analysis of Muslim Immigrant Women - Ali, Farah (Universidad Pedagógica y Tecnológica de Colombia, 2020)
Owing to the continuous influx of immigration in Catalonia, multilingualism has become the bedrock of this region. Still, Catalan and Spanish remain the dominant languages of everyday communication and immigrants are faced with the challenge of adopting both Spanish and Catalan linguistic identities. This dual acculturation process can span across generations and can be impacted by a variety of sociocultural factors. Additionally, motivation to acculturate can be rooted in individuals’ own complex identities that are constructed in different sociocultural contexts, a connection that Norton (2000) has conceptualized as “investment.” This study examines Muslim immigrant women’s investment in Spanish and Catalan, as well as the sociocultural factors that play a role in this investment. The present study relies on data gathered from 34 Muslim immigrant women from diverse geographic backgrounds. Findings indicate that a variety of factors impact informants’ relationship with their linguistic identities, often in disparate ways. Furthermore, first and second-generation informants presented distinct experiences with acculturation, suggesting that it is a transgenerational process. Finally, informants’ responses also suggest that their linguistic investment is informed by their gendered and religious identity.